Образность как циклообразующий принцип в романах о Гарри Поттере Дж. К. Роулинг - Зайцева, А.В.; Ищенко, Н.А. (Культура народов Причерноморья, 2014)
Одним из самых заметных событий в литературном мире рубежа ХХ-ХХI вв. стало
появление книг английской писательницы Джоан Роулинг о Гарри Поттере. В работе проведено
исследование образности как циклообразующего принципа в романах о Гарри Поттере.
Охарактеризовано понятие системы персонажей в художественном произведении, проанализирована
специфика структуры персонажной системы. Рассмотрены функции героев в художественном мире
романов и способы описания персонажей. Значительное место занимает характеристика главных,
второстепенных и эпизодических персонажей книг о Гарри Поттере. Однією з найпомітніших подій в літературному світі рубежу ХХ-ХХІ ст. стала поява книг
англійської письменниці Джоан Роулінг про Гаррі Поттера. У роботі проведено дослідження
образності як циклообразуючого принципу в романах про Гаррі Поттера. Охарактеризовано поняття
системи персонажів у художньому творі, проаналізована специфіка структури персонажної системи.
Розглянуто функції героїв у художньому світі романів і способи опису персонажів. Значне місце займає
характеристика головних, другорядних та епізодичних персонажів книг про Гаррі Поттера. One of the most significant events in the literary world in the late twentieth early twenty-first
centuries was the emergence of the author’s series about Harry Potter by Joanne K. Rowling. However, despite
the fact that the books appeared on the literary market in the late 90s of last century, the author’s cycle is still
not adequately explored, as a specific phenomenon of modern literature. The author’s series about Harry Potter
is a very interesting area to explore. It attracts linguist’s and specialist’s in study of literature attention by its
originality in many aspects. The article presents the results of the complex analysis of imagery as a cycle
component of the author’s series by J. K. Rowling. Images in “Potteriana” play a very important role for a
deeper understanding of the work. The character’s system is unique, specific multi-layered and because of them the author’s series is the organic whole. Analysis and interpretation of features of construction of the characters
help to understand artistic intent of the author. The purpose of the article is to prove that imagery is the main
cycle component in the series. There have been characterized the concept of the character’s system and the
specific character of the structure of the characters. The considerable part of the paper takes the characteristics
of the main secondary and incidental characters of the Harry Potter series. It was determined that the system of
characters in the cycle includes a huge number of characters that can be divided into several representative
groups that take part in the creation of event-semantic content of the artistic world of "Harry Potter".